Random Amplification of Polymorphic DNA Analysis for Genetic Characterization of Two Breeds of Dogs, German Shepherd and Japanese Spitz - Joshsi, Jarina; Manandhar, Lumanti; Shrestha, Patima; Gupta, Rani; Manadhar, Rojlina; Shrestha, Smita (Nepal Journal of Science and Technology, 2013)
Random amplified polymorphic DNA (RAPD) markers were used to study genetic diversity in dog samples belonging to populations of German Shepherd and Japanese Spitz. A total of twelve samples were typed using eight RAPD primers. Out of eight primers, three primers gave result in six individuals of dogs. The phylogenetic tree constructed by the neighbor joining method based on Nei. Original measures revealed highest genetic identity found in German Shepherd as 0.9444 and highest genetic distance as 1.2809. The analysis predicts the number of polymorphic loci as 15 and the percentage of polymorphic loci as 83.3. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 73-78 DOI: http://dx.doi.org/10.3126/njst.v13i2.7717